2016
DOI: 10.1371/journal.pone.0160521
|View full text |Cite|
|
Sign up to set email alerts
|

Cystathionine-Gamma-Lyase Gene Deletion Protects Mice against Inflammation and Liver Sieve Injury following Polymicrobial Sepsis

Abstract: BackgroundHydrogen sulfide (H2S), produced by the activity of cystathionine-gamma-lyase (CSE), is a key mediator of inflammation in sepsis. The liver sinusoidal endothelial cells (LSECs) are important target and mediator of sepsis. The aim of this study was to investigate the role of CSE-derived H2S on inflammation and LSECs fenestrae in caecal-ligation and puncture (CLP)-induced sepsis using CSE KO mice.MethodsSepsis was induced by CLP, and mice (C57BL/6J, male) were sacrificed after 8 hours. Liver, lung, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 46 publications
5
34
0
Order By: Relevance
“…This modulation of immunity is also supported by decreased levels of cytokines responsible for controlling bacterial infections, such as IL-1β, IL-6, IL-9, IL-12, TNF-α, IL-17, and IFN-γ (29,39), observed in the serum of the WT mice. The data point to H 2 S as a regulator of innate and adaptive immunity during Mtb infection and our findings agree with studies showing that CSE-deficient mice are resistant to sepsis and associated inflammatory responses (16).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This modulation of immunity is also supported by decreased levels of cytokines responsible for controlling bacterial infections, such as IL-1β, IL-6, IL-9, IL-12, TNF-α, IL-17, and IFN-γ (29,39), observed in the serum of the WT mice. The data point to H 2 S as a regulator of innate and adaptive immunity during Mtb infection and our findings agree with studies showing that CSE-deficient mice are resistant to sepsis and associated inflammatory responses (16).…”
Section: Discussionsupporting
confidence: 92%
“…The strong CSE and MPST signals within the TB lungs raises the provocative idea that H 2 S could also function as an in vivo fuel source for Mtb. Not surprisingly, as was demonstrated in this study, overproduction of H 2 S is also associated with several other clinicopathological manifestations, including sepsis and associated inflammation (12)(13)(14)(15)(16). As was previously demonstrated in different inflammatory models, increased levels of H 2 S inhibit production of proinflammatory mediators, such as IL-1β, IL-6, TNF-α, NO, and mitochondrial ROI, but stimulate production of the antiinflammatory cytokine IL-10 in a dose-dependent manner (57)(58)(59), which supports our observations in Mtb-infected WT mice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, Bhatia et al (2005) demonstrated that the treatment with DL-propargylglycine, a CSE inhibitor, significantly reduced the severity of pancreatitis and lung injury induced by caerulein. Similarly, in caecal-ligation and puncture-induced sepsis mice model, CSE gene deletion alleviated the liver and lung injury and reduced inflammation along with the activation of ERK1/2 and NF-κB pathway ( Gaddam et al, 2016 ). Those results suggested that H 2 S played a role as pro-inflammatory cytokines.…”
Section: Sulfhydration Mediates H 2 S-induced Biolmentioning
confidence: 99%
“…Several studies reported that H 2 S gives protection against ALI (Campos et al 2016;Zhang et al 2016). But, Qu et al (2014); Gaddam et al (2016) have found the reverse. Due to these antagonistic results, the present research was done to evaluate the effect of NaHS that serves as a donor of H 2 S and PAG which is an irreversible inhibitor of the H 2 S synthesizing enzyme CSE on ALI produced by LPS.…”
Section: Introductionmentioning
confidence: 98%